The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.2337/diacare.28.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Active Call Center Treatment Support (PACCTS) to Improve Glucose Control in Type 2 Diabetes

Abstract: OBJECTIVE -To determine whether Pro-Active Call Center Treatment Support (PACCTS), using trained nonmedical telephonists supported by specially designed software and a diabetes nurse, can effectively improve glycemic control in type 2 diabetes. RESEARCH DESIGN AND METHODS -A randomized controlled implementationtrial of 1-year duration was conducted in Salford, U.K. The trial comprised 591 randomly selected individuals with type 2 diabetes. By random allocation, 197 individuals were assigned to the usual care (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
96
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 19 publications
4
96
0
1
Order By: Relevance
“…Since no feedback whatever (acknowledgement, encouragement, intervention, education) was returned to the patient using the system, we suggest that this favourable drop may be attributed to a Hawthorne (placebo) effect caused by merely requiring patients to report their blood glucose values on a daily basis to a passive call centre. Young et al [20] achieved identical improvements in HbA 1 c in type 2 diabetes but using a personalised telephone care centre support system, known as the Pro-Active Call Center Treatment Support, which featured two telecarers supported by a diabetes nurse specialist. It is encouraging that when the predictions afforded by the engine are acted upon [5], large and significant reductions in the rates of hypoglycaemia and major improvements in glycaemic control can be realised.…”
Section: Discussionmentioning
confidence: 99%
“…Since no feedback whatever (acknowledgement, encouragement, intervention, education) was returned to the patient using the system, we suggest that this favourable drop may be attributed to a Hawthorne (placebo) effect caused by merely requiring patients to report their blood glucose values on a daily basis to a passive call centre. Young et al [20] achieved identical improvements in HbA 1 c in type 2 diabetes but using a personalised telephone care centre support system, known as the Pro-Active Call Center Treatment Support, which featured two telecarers supported by a diabetes nurse specialist. It is encouraging that when the predictions afforded by the engine are acted upon [5], large and significant reductions in the rates of hypoglycaemia and major improvements in glycaemic control can be realised.…”
Section: Discussionmentioning
confidence: 99%
“…There was an example of a negative impact of linkages: the PACCTS study used information from the patients' e-health records to trigger telephone calls. 40 Patients would visit their GP and have HbA1c tests and if the results were above 9% they received a monthly call and this reduced to three monthly if HbA1c was 7%. Patients may not have been aware that this information had triggered the telephone calls and 8.2% withdrew because they could not cope with the calls.…”
Section: Discussionmentioning
confidence: 99%
“…Only one 46 of seven studies using planned coaching reported improvements in adherence compared with 4/4 using reactive coaching. 21,33,35,[38][39][40] …”
Section: Improvements In Behaviour Self-efficacy and Health Statusmentioning
confidence: 99%
See 2 more Smart Citations